Zwei beitrage zum problem der bevolkerungsstruktur von Gross-Athen - Crueger, Eberhard (The Greek Review of Social Research, 1971)
As a contribution to the step by step clarification of the difficult and complex demographical conditions of Greater Athens two results of an investigation concerning the population structures of 50 of the 57 communities belonging to the agglomeration will be shown : 1 ) some remarks on the distribution of the immigrants of the years 1951 - 1961 within the agglomeration; 2) a typification and local articulation of the demographical structures of Greater Athens. Part I : Basis of the investigation are the results of the population censuses of 1951 and 1961 published by the National Statistical Service of Greece, which allow work with exact and large figures. However, due to the insufficient questionnaires as well as to the manner of publication, the material is not sufficiently differentiated with regards to the factors of investigation and the local articulation. (An example: the figures were published only for administrative units as a whole, without considering—at least with regards to the larger communities—necessary further split-ups). Thus on this basis investigations on the population structures can only lead to insufficient results. We shall be restricted to these preliminary results until there will be published differentiated and more complete material which will also satisfy the needs of the population geographer. Part II : The population inflow adds a great deal to the rapid growth of Greater Athens. Because of the decisive impact of population inflow on the population structure of a town generally, it is desirable to know the repartition of the immigrants within the agglomeration of Athens. However, exact figures of the immigrants in the different communities are not available. The author depicts a method according to which figures of the immigrants of the years 1951 - 1961 can be calculated upon: 1) Population of 1951 plus population 1961 divided by 2 shows the average population of 1951/61: 2) Average population 1951/61 divided by 1.000 multiplied by the natural increase rate of 1961 multiplied by 10 shows the absolute natural population increase of 1951/61: 3) Population 1961 minus population 1951 minus absolute natural population increase 1951/61 shows the approximate absolute number of immigrants. Based on this method fig. 2 gives the relative share of the immigrants in the total population of each single community. However, this method involves some problematic factors which can only be eliminated to a certain extent and of which the most important are : the rates of the natural population increase can only be fixed for the year 1961, inner-town mobility is unknown to a large extent, and others. The results which are attained by this method can be only regarded as estimates (see legend fig. 2). Taking into account these sources of possible error, it is completely impossible to make statements on some of the communities. This is followed by a short interpretation of fig. 2. Part III : Typification and local repartition of the demographical structures of 50 communities of Greater Athens. Because of the insufficient statistical material, the results can be regarded only as an attempt to enable a first orientation. By particular analysis (not related in this paper) the different structures of the communities were examined. By a comparative examination of these particular analysis and a combination of their results those districts of Greater Athens were determined upon, in which communities proved equal or very similar in their population structure (fig. 3). Based on the statistic material the following items could be included in the analysis in particular (commented upon in the essay with regards to their usefulness and completeness): structure of age, natural population mobility, repartition of sex, percentage of economically actives (separately for men and women), education (percentage of illiterates), immigration (see part II, plus the economic activity of the immigrants 1956-61), population increase 1951-1961, housing conditions (equipment of the localities). The table will enable one to imagine the numerical value of the terms which are used in the interpretation of fig. 3 «low», «middle», «high». Main types of population structure are distinguished (A - D), which are themselves split up in various sub - types (pointed out by figures, e.g. A/l, A/2) respectively special types (e.g. A/2.1). Some extreme cases (ax - d) which can be added to several types are treated separately. The full interpetation of fig. 3 is condensed to a short characterization of the 4 main types : type A signifies a young, dynamic population of lower social status, which mainly consists of recent immigrants. The structure of this population shows typical symptoms of badly integrated immigrant-regions, as they often develop at the outskirts of quickly growing large towns. The most extreme samples are to be found in the sub - type A/l. Type B, too, is to be found in only recently populated regions. However, there is an older, well settled population of upper and middle class citizens in more preferable residential areas. The numerous feminin service personnel—mainly immigrants— represent an important factor in the population. Type C is located in communities of the interior parts of the agglomeration, which are densely and already for a long time populated. It consists of an older, fixed, and long established population of most different social classes, stagnating in its development. Certain variables vary greatly among the different sub-types. Type D consists of a region where only recently were still rather rural suburbs of Athens. This part most likely will be very important for the future development of the agglomeration; the structures of the still fixed, older middle-class populations of these communities are undergoing different phases of strongly transforming developments. The future development tends on one hand towards the conditions of the immigrant - regions type A/3, on the other hand—in the regions of especially beautiful scenery—towards an approach to type B. The extreme cases result of the overlapping of population structures in adjoining regions. They thus could at the same time be taken to several population types. The last table shows—only for an orientation